Building integrated agriculture information modelling (BIAIM): An integrated approach towards urban agriculture. (February 2018) - Khan, Rana; Aziz, Zeeshan; Ahmed, Vian
Highlights: The relationship between plants and environmental is studied and Tomato as a reference crop is selected. The impact of environmental factors on the germination of tomato seedling is simulated and assessed. Controlled environmental agriculture and building integrated agriculture is discussed. The integration of agriculture and Building Information Modelling platform is proposed. A Building integrated agriculture information modelling plugin for building information modelling software is developed. Abstract: Urbanisation is transforming human societies in many ways. Besides bringing benefits to people in cities, it also has negative impacts such as food security. One way to meet the challenge is urban agriculture; however, traditional agricultural practices are not suitable within urban areas due to limited availability of land. Therefore, the alternative option is to grow crops inside or on top of buildings, e.g. building integrated agriculture (BIA). But, there is limited research and information available for designers and planners to design such buildings. The presented research project bridges the gap between agriculture and architecture by proposing a building integrated agriculture information modelling tool in integration with Building information modelling. The plugin tool has data on plants' requirements and automatic response to environmental factors. Environmental factors include temperature, light, water, nutrients, air, humidity, spacing and support. In this paper, seasonal tomato is selected as a reference crop, and the impact of environment (temperature, light, water, nutrients and spacing) on its health is discussed and simulated for germination stage. The undertaken project contributes to the concept of BIA and BIM maturity level, which would help to design an optimum environment building for plants.